Systematically Measuring Ultra-diffuse Galaxies (SMUDGes). V. The Complete SMUDGes Catalog and the Nature of Ultradiffuse Galaxies - Dennis Zaritsky; Richard Donnerstein; Arjun Dey; Ananthan Karunakaran; Jennifer Kadowaki; Donghyeon J. Khim; Kristine Spekkens; Huanian Zhang (The Astrophysical Journal Supplement Series, 2023)
We present the completed catalog of ultradiffuse galaxy (UDG) candidates (7070 objects) from our search of the DR9 Legacy Survey images, including distance and total mass estimates for 1529 and 1436 galaxies, respectively, that we provide and describe in detail. From the sample with estimated distances, we obtain a sample of 585 UDGs ( μ _0, _g ≥ 24 mag arcsec ^−2 and r _e ≥ 1.5 kpc) over 20,000 square degrees of sky in various environments. We conclude that UDGs in our sample are limited to 10 ^10 ≲ M _h / M _⊙ ≲ 10 ^11.5 and are on average a factor of 1.5–7 deficient in stars relative to the general population of galaxies of the same total mass. That factor increases with increasing galaxy size and mass up to a factor of ∼10 when the total mass of the UDG increases beyond M _h = 10 ^11 M _⊙ . We do not find evidence that this factor has a dependence on the UDGs large-scale environment.